Mechanisms modulating the activities of intestinal stem cells upon radiation or chemical agent exposure. (10th January 2022) - Liao, Zebin; Hu, Changkun; Gao, Yue
Abstract: Intestinal stem cells (ISCs) are essential for the regeneration of intestinal cells upon radiation or chemical agent damage. As for radiation-induced damage, the expression of AIM2, YAP, TLR3, PUMA or BVES can aggravate ISCs depletion, while the stimulation of TLR5, HGF/MET signaling, Ass1 gene, Slit/Robo signaling facilitate the radio-resistance of ISCs. Upon chemical agent treatment, the activation of TRAIL or p53/PUMA pathway exacerbate injury on ISCs, while the increased levels of IL-22, β-arrestin1 can ease the damage. The transformation between reserve ISCs (rISCs) maintaining quiescent states and active ISCs (aISCs) that are highly proliferative has obtained much attention in recent years, in which ISCs expressing high levels of Hopx, Bmi1, mTert, Krt19 or Lrig1 are resistant to radiation injury, and SOX9, MSI2, clusterin, URI are essential for rISCs maintenance. The differentiated cells like Paneth cells and enteroendocrine cells can also obtain stemness driven by radiation injury mediated by Wnt or Notch signaling. Besides, Mex3a-expressed ISCs can survive and then proliferate into intestinal epithelial cells upon chemical agent damage. In addition, the modulation of symbiotic microbes harboring gastrointestinal (GI) tract is also a promising strategy to protect ISCs against radiation damage. Overall, the strategies targeting mechanisms modulating ISCs activities are conducive to alleviating GI injury of patients receiving chemoradiotherapy or victims of nuclear or chemical accident.